1962
DOI: 10.1111/j.2044-8295.1962.tb00824.x
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Growth of Some Logical Structures

Abstract: A number of experiments of the type suggested by Piaget & Inhelder's book La genèse des structures logiques élémentaires were given to a population of primary and educationally subnormal (E.S.N.) special school children. The findings among the former group generally confirm those of the Geneva school. It has been possible to extend Piaget & Inhelder's findings by giving a number of tests to the same children, and by making a comparative study of primary and E.S.N. school pupils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
13
1

Year Published

1966
1966
1986
1986

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 0 publications
5
13
1
Order By: Relevance
“…Inhelder and Piaget (1 964) found that this sort of mistake is more frequent when the quantified term concerns colour rather than shape. It is still further enhanced when the term concerns weight (Lovell, Mitchell, and Everett, 1962). Hence, it seems that performance is better with more concrete, or more graphic, terms: similarly, Markman and Seibert (1976) have found enhanced set-theoretic judgements when the superordinate set is one that is characteristically relational, such as a family ;and Donaldson (1978, p. 67) has shown that the saliency of some aspect of the situation may also mislead children.…”
Section: Premisesmentioning
confidence: 99%
“…Inhelder and Piaget (1 964) found that this sort of mistake is more frequent when the quantified term concerns colour rather than shape. It is still further enhanced when the term concerns weight (Lovell, Mitchell, and Everett, 1962). Hence, it seems that performance is better with more concrete, or more graphic, terms: similarly, Markman and Seibert (1976) have found enhanced set-theoretic judgements when the superordinate set is one that is characteristically relational, such as a family ;and Donaldson (1978, p. 67) has shown that the saliency of some aspect of the situation may also mislead children.…”
Section: Premisesmentioning
confidence: 99%
“…Past research in classification tasks has focused on how children learn (a) to form one class (Bruner & Olver, 1963;Inhelder & Piaget, 1959;Lovell, Mitchell, & Everett, 1962;Morf, 1959;Vigotsky, 1962), (b) to change their criteria for categorization (Heald & Marzolf, 1953;Lovell, Mitchell, & Everett, 1962), and (c) to compare the size and contents of different classes (Dodwell, 1962;Hyde, 1959;Inhedler & Piaget, 1959;Piaget, 1952).…”
Section: University Of Rochestermentioning
confidence: 99%
“…Piaget's findings which have been supported by several studies (Dodwell, 1968;Elkind, a, b, c, 1964Kofsky, 1968;Lovell, Mitchell, & Everett, 1962;Lovell & Ogilvie, 1960Uzgiris, 1964;Wohlwill, 1960) indicate that conservation of substance develops first followed by conservation of weight and then volume. Furthermore, many of the training studies have shown that while there has been some success with certain training procedures designed to help a child understand a particular conservation task, there is mixed evidence with respect to whether or not transfer of learning occurs.…”
mentioning
confidence: 75%